Urgent prevention in cardiovascular disease - V. V. Ruksin (Кардиоваскулярная терапия и профилактика, 2005)
In Russia, high prevalence of cardiovascular disease (CVD) and objective difficulties in its primary and secondary prevention make actual the issue of creating a new prevention branch – urgent CVD prevention. Urgent prevention includes: prevention of CVD pathology when its risk is increasing; patient self-help manipulations in case of emergency, according to doctor-created, individual programs; early, complex medical support according to unified recommendations; additional measures on preventing cardiovascular emergency complications. Creating such a new preventive branch should facilitate utilization of present limited resources and improve CVD management results.